Effects of Environmental Enrichment and Physical Activity on Neurogenesis in Transgenic PS1/APP Mice - Catlow, Briony J (2008)
Rodents exposed to environmental enrichment show many differences, including improved cognitive performance, when compared to those living in standard (impoverished) housing. The purpose of the present study was to determine if a selective increase in neurogenesis occurred in cognitively-protected Tg mice raised in an enriched environment compared to those reared in physical activity housing. At weaning, double Tg APP+PS1 mice were placed into one of three environments: complete environmental enrichment (CE), enhanced physical activity (PA), or individual, impoverished housing (IMP). At 9–10 months of age, Tg mice were injected with BrdU (100 mg/kg BID) followed by euthanasia either 24 hrs or two weeks after the last injection. Unbiased estimates of BrdU positive cells in the hippocampal subgranular zone revealed a significant increase in cellular proliferation in Tg mice raised in CE or PA compared to Tg mice reared in IMP housing. However, counts of BrdU birth-dated cells two weeks after labeling showed no difference among the three groups, indicating decreased survival of cells in those groups (CE and PA) with higher cellular proliferation rates in the neurogenic niche. Counts of calretinin-expressing cells, a marker of immature neurons, also indicated no difference among the three groups of mice. In view of our prior study showing that enhanced cognitive activity (but not enhanced physical activity) protects Tg mice against cognitive impairment, the present results indicate that increased generation and survival of new neurons in the hippocampal dentate gyrus is not involved with the cognitively-protective effects of complete CE in Alzheimer’s transgenic mice.